Application of gravity center method and AHP method for locating a garage of a dangerous goods transporter - Bastos, Brenda Schulz; Venturin, Arthur Vieira; Gomes, Thiara Cezana (Brazilian Journal of Production Engineering, 2025)
Brazil’s transportation matrix is ​​predominantly road-based, and this mode of transportation is of great importance to the country. When it comes to vehicles that transport hazardous cargo, such as trucks that supply gas stations, high competitiveness and tight margin operations are noteworthy. In this context, cost reduction is necessary through a fundamental element in the logistics strategy planning/supply chain management triangle: location. Thus, the objective of the research is to define the location for the installation of a garage for a fuel transportation company, based on the application of the Center of Gravity and Analytic Hierarchy Process (AHP) methods. To do so, it was necessary to understand the company’s context, collect data, apply the methods and, finally, analyze the results. Aspects such as transportation costs, location and volume moved by suppliers and customers were considered, in addition to qualitative criteria such as safety and accessibility. The implementation of both methods proved effective in assisting decision-making to indicate the best location for the company’s new garage. The importance of analyzing quantitative and qualitative criteria during the process of locating facilities is highlighted.